Digital Leap Workshop: Build Your Online Store Boost Your Sales - Sri Harjanto; Retno Tri Vulandari; Suryanti Galuh Pravitasari (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2026)
During the "Digital Leap Workshop: Build Your Online Store, Boost Your Sales" community service activity held at Rumah Quran Qolbun Salim, a key focus was the use of TikTok Shop and the Affiliate Program as digital sales and marketing tools for elderly participants and retirees. The activity demonstrated that participants gained a fundamental understanding of TikTok Shop as a platform integrating e-commerce with video content, as well as the TikTok Affiliate program as an opportunity to generate income without needing to own their own products. Participants were introduced to the initial steps of account creation, product selection, simple content creation, and the mechanics of sales commissions. They showed growing interest and enthusiasm for these relatively easy and flexible sales and promotional models. The material was presented using a practical, step-by-step approach, allowing participants to follow along at their own pace. This activity offered a realistic and suitable digital business alternative for the elderly and retirees, while opening up opportunities for additional income through the wise and sustainable use of TikTok Shop and affiliate programs.